Reducing elbow pain and improving pull-up strength in an elite Chinese female weightlifter through a specific low volume program - Ren, D. C. (Journal of Australian Strength and Conditioning, 2019)
A low volume, high intensity pull-up program, coupled with some of the dynamic, propioceptively challenging warm-up exercises, increased pull-up strength by ~18%1RM, increased power snatch capabilities, overhead lockout stabilisation strength; reduced nagging elbow pain in an elite Chinese female Weightlifter.